Sustainability of a first-mover strategy in the emerging Norwegian snow crab industry - Bertheussen, Bernt Arne; Nøstvold, Bjørg Helen (Ocean & Coastal Management, 2020)
The initial stage of the emerging Norwegian snow crab (SC) industry was characterized by excessive optimism, and this case study explores whether the early entrants have gained sustainable first-mover advantages. Unfortunately, the investments have not been profitable as the firms made a yearly average negative profit of more than 10% in the period examined. Accordingly, the early entrants have so far suffered first-mover disadvantages. Nevertheless, the modest economic start may be bad at predicting the future wealth-creating potential. This, however, will require the SC population of the Barents Sea to increase sharply. It will also require that the nations involved in fishing SC agree on the distribution of the total quota between them. Another institutional requirement is that a system of catch shares (e.g. individual tradeable quotas) is introduced in the Norwegian SC fishery to protect the strategic position of the players from outside intruders, and also efficiently block the rivalry between them. The SC fishers are engaged in an extremely risky business with a significant financial loss potential. In addition to risks related to the resource base and to national and international regulations, there are large risks associated with how SCs in the Barents Sea can be best captured, processed and sold. As a consequence, the firms participating in SC fishing need significant financial reserves to cover any future losses. Without such reserves, they must either choose to withdraw from the industry and consider the inflicted losses as sunk cost as some have already done, or they will risk bankruptcy.